2011
DOI: 10.5021/ad.2011.23.4.468
|View full text |Cite
|
Sign up to set email alerts
|

IL-31 Serum Protein and Tissue mRNA Levels in Patients with Atopic Dermatitis

Abstract: BackgroundSevere pruritus is the primary symptom in atopic dermatitis (AD). Recently, the novel cytokine IL-31 has been implicated in the itching associated with AD.ObjectiveWe performed this study to determine whether IL-31 serum levels are elevated in AD patients and to better characterize the relationship between serum IL-31 level and other established laboratory parameters.MethodsWe recruited 55 AD patients, 34 with allergic type AD and 21 with non-allergic type AD, and 38 healthy, non-atopic controls. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
47
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 19 publications
5
47
2
5
Order By: Relevance
“…45 And a recent cross-sectional study of Nygaard et al that included 163 adults and children with AD, was unable to confirm the correlation between serum IL-31 and disease severity. 46 Kim et al found that IL-31 mRNA expression is higher in biopsies from AD patients with high pruritus scores compared to patients with low pruritus scores, 47 suggesting that measurement of IL-31 in skin may be a more relevant measure for itch. Although IL-31 expression patterns in skin biopsies may also be extremely helpful in stratification, skin biopsies are invasive, require trained personnel and specialized labs.…”
Section: Biomarker For Itchmentioning
confidence: 99%
“…45 And a recent cross-sectional study of Nygaard et al that included 163 adults and children with AD, was unable to confirm the correlation between serum IL-31 and disease severity. 46 Kim et al found that IL-31 mRNA expression is higher in biopsies from AD patients with high pruritus scores compared to patients with low pruritus scores, 47 suggesting that measurement of IL-31 in skin may be a more relevant measure for itch. Although IL-31 expression patterns in skin biopsies may also be extremely helpful in stratification, skin biopsies are invasive, require trained personnel and specialized labs.…”
Section: Biomarker For Itchmentioning
confidence: 99%
“…In this study, we report on our studies to clarify further the molecular and functional consequences of IL-31 signaling in keratinocytes. Primary normal keratinocytes express very low levels of IL-31RA, which can be induced by IFN-g (33)(34)(35)(36)41). However, such treatment has additional consequences, including cell cycle arrest, making it difficult to distinguish between IFN-g-and IL-31-specific effects.…”
mentioning
confidence: 99%
“…IL-31 belongs to the IL-6 family of proinflammatory cytokines and signals through heterodimeric receptors composed of the oncostatin M receptor and the IL-31-specific receptor IL-31RA (30)(31)(32). IL-31 expression is increased in lesions and serum of patients with AD and correlates with disease severity (30,(33)(34)(35)(36). Furthermore, distinct haplotypes of the IL31 gene are associated with AD (27,37,38).…”
mentioning
confidence: 99%
“…As in the case of IL-13, transgenic overexpression of IL-31 also induced severe pruritus and dermatitis in mice [144]. Further supporting its role, increased expression of IL-31 was found both in an atopic mouse model [145] and in AD patients [146,147] in good correlation with the scratching behavior in mice [148] and the symptom severity in humans [149,150]. The exact pruritogenic mechanism of action of IL-31 is still unclear although IL-31 receptors were detected on a fraction of small diameter sensory neurons [151] as well as on normal human epidermal keratinocytes (NHEKs) [152].…”
Section: Inflammatory Mediators As Peripheral Itch Sensitizersmentioning
confidence: 52%